Resilience and Its Contributing Factors in Adolescents in Long-Term Residential Care Facilities Affiliated to Tehran Welfare Organization - Manijeh Nourian; Farahnaz Mohammadi Shahboulaghi; Kian Nourozi Tabrizi; Maryam Rassouli; Akbar Biglarrian (Shiraz University of Medical Sciences, 2016)
Background: Resilience is a quality that affects an individual's ability to cope with tension. The present study was conducted to determine resilience and its contributing factors in high-risk adolescents living in residential care facilities affiliated to Tehran Welfare Organization in order to help develop effective preventive measures for them. Methods: The present descriptive study was conducted on 223 adolescents living in 15differentgovernmental residential care centers in 2014. Participants were selected through convenience sampling. The data required were collected via the Wagnild and Young Resilience Scale with content validity (S-CVI=0.92) and a reliability of α=0.77 and r=0.83 (P<0.001). The data obtained were analyzed in SPSS-20 using descriptive and inferential statistics including Chi-square test, independent t-test and ANOVA. Results: The adolescents' mean score of resilience was 84.41±11.01. The level of resilience was moderate in 46.2% of the participants and was significantly higher in the female than in the male adolescents (P=0.006); moreover, the score obtained was lower in primary school children as compared to middle school and high school students (P<0.001). Conclusion: Directors of care facilities and residential care personnel should adopt preventive resilience-based strategies in order to optimize resilience among adolescents, particularly the male. It is important to provide a basis to prevent adolescents' academic failure and place a stronger value on education than the past.